Evaluation of the oncolytic property of recombinant Newcastle disease virus strain R2B in 4T1 and B16-F10 cells in-vitro. (October 2021) - Ramamurthy, Narayan; Pathak, Dinesh C.; D'Silva, Ajai Lawrence; Batheja, Rahul; Mariappan, Asok Kumar; Vakharia, Vikram N.; Chellappa, Madhan Mohan; Dey, Sohini
Abstract: Recombinant Newcastle disease virus vectors have gained a lot of interest for its oncolytic virus therapy and cancer immune therapeutic properties due to its selective replication to high titers in cancer cells. The aim of this study was to find out the oncolytic effects of mesogenic recombinant NDV strain R2B-GFP on murine mammary tumor cell line 4T1 and murine melanoma cell line B16-F10. The anti-tumor effects of R2B-GFP virus were studied via expression of virus transgene GFP in cancer cells, evaluating its cytotoxicity and cell migration efficacies by MTT and wound healing assays respectively. In addition, the underlying apoptotic mechanism of R2B-GFP virus was estimated by TUNEL assay, colorimetric estimation of Caspase-3, 8 and 9 and the estimation of Bax to Bcl-2 ratio. The results showed a significant decrease in viability of both 4T1 and B16-F10 cells infected with R2B-GFP virus at 0.1 and 1 MOI. R2B-GFP virus could significantly induce apoptosis in the 4T1 and B16-F10 cells as compared to the uninfected control. Further, a flow cytometry analysis on apoptotic cells percentage and mitochondria membrane permeability test was also studied in R2B-GFP virus treated 4T1 and B16-F10 cell lines. The R2B-GFP virus caused an increase in loss of mitochondrial membrane permeability in both 4T1 and B16-F10 cells indicating the involvement of mitochondrial regulated cell death. Thus, the recombinant virus R2B-GFP virus proved to be a valid candidate for oncolytic viral therapy in 4T1 and B16-F10 cells. Highlights: Oncolytic effect of recombinant NDV stain R2B-GFP studied in 4T1 and B16-F10 cells. R2B-GFP decreased the viability at 0.1 and 1 MOI. An increase in loss of mitochondria membrane permeability was observed. R2B-GFP virus proved to be a valid candidate for oncolytic viral therapy.